Ética y design : responsabilidades éticas en el proyecto de design - Ortiz Sánchez, Yvonne, 1985- (2014)
In order to identify the ethical responsabilities of the design process, it is a priority to develop this dissertation. It seeks to understand the importance of design from the point of view of a producer of “material culture”, and the need to introduce ethics in the process of design. Also, by implementing ethical responsabilities in the design process, it generates the development of objects that have ethical commitment, and increases critical thinking in the designer. The design as a process, activity, and profession in the service of the humans; is capable of transforming the current reality with environmental and social problems, to achieve well-being in many aspects not only for present but future generations. This thesis contextualizes both ethical responsabilities and the design process; the design itself and its importance through the Culture of Design; and ethics through philosophical thinking, to establish a bond and a common purpose. Not only that, but also talks about the theory and concept of design and ethics, through the analysis of the proposals that have been published on the subject. Additionally, this research helps find the places in wich ethical responsabilities influences design. In order to obtain these findings; we elaborated a synthesis of the problem, what is necessary, and the function of three different fields: design, ethics and the social and environmmental context, each one of them to submit a formal proposal. The proposal was defined in three areas: Design Responsibilities, Responsibilities of the Design project and Designer Responsibilities, each one of these areas to define the priorities of the designers. We propose these three areas, because the design is the material result of the process, the designer is the person that develops the object by the process and the design project is the process itself. To evaluate our proposal, we publish surveys that helped us to categorized the priorities and add suggestions to complement our work. The responses obtained, ratified both tendencies of authors such as our thinking